“We live with it”: portuguese patients and relatives’ perspectives of Physiotherapy role in the course of Huntington’s Disease: a qualitative study - Agostinho, Inês Sofia Mendes (2023)
Background: Huntington's Disease is a hereditary autosomal dominant, and neurodegenerative condition. It combines motor, cognitive and behavioural disturbances. Nowadays, Physiotherapy for Huntington´s encompasses interventions such as exercise, physical activity promotion, balance, task-specific training and education. It seeks to enable patients with impairments, activity limitations and participation restrictions to reach their optimal functional level. However there are just a few articles that relate Huntington's Disease with Physiotherapy, and as far as we know there is none in Portugal that truly evaluates the patient's and families’ needs and how Physiotherapy helps. Purpose: Understand how Physiotherapy helps in the life, challenges and problem-solving of Huntington’s Disease patients and their relatives. Additionally, understand what we can change in Physiotherapy to improve the integration of patients in society. Methods: A phenomenology qualitative work, with semi-structured, audio and video record interviews, made preferentially through APDH and other contacts. Interviews were transcribed and analysed following the theory of thematic analysis to identify salient themes. Results: A total of 18 participants were interviewed (6 patients and 12 relatives). Five themes derived: Objectives and ICF (Theme 1), Society and HD (Theme 2), Health Care and Needs in HD (Theme 3), Physiotherapy and HD (Theme 4), and Family and HD (Theme 5). Conclusions: Physiotherapy represents a powerful tool in the lifelong management of Huntington’s Disease. It seems to have a role in daily activities, autonomy, self-confidence, family management and strength and walking capacity. Although there is a need for improving the human-centred approach, to meet patients' and family members' specific objectives in order to reduce their limitations in social participation. Future studies should evaluate the quality and the content of the Physiotherapy sessions.